(untitled) (Research, Society and Development, 2023)
Eating disorders are a significant health issue among Brazilian teenagers, and awareness, education, and action are essential to effectively address this challenge. The physical and mental well-being of teenagers should be prioritized, and everyone has a role to play in promoting healthy eating habits and preventing these disorders. In this context, the aim of this research was to provide a deeper understanding of this issue that affects the health and well-being of young Brazilians. To do so, a literature review approach was adopted with the objective of identifying and summarizing the main ideas and concepts related to the topic under discussion. After a careful analysis of titles and abstracts and a thorough reading of the studies, 10 articles were selected as the basis for this review. The results of this literature review revealed that the most prevalent eating disorders among adolescents in Brazil are anorexia nervosa, bulimia nervosa, and binge-eating disorder. Additionally, they highlighted the significant influence of social pressure and aesthetic standards on the manifestation of these disorders. These findings underscore the urgent need for preventive interventions and awareness campaigns to address this public health issue and promote the physical and mental health of teenagers in the country. It is worth noting that obtaining more comprehensive and up-to-date data can contribute to the development of more effective prevention and treatment strategies.